Mediterranean forest policy beyond the Paris Climate Agreement. (January 2022) - Andrea, Veronika
Abstract: The nature and complexity of forest ecosystems in the Mediterranean region imply the necessity to implement robust and integrated policies, strategies, and special measures to meet the commitments set in Article 5 of the Paris Agreement. This study aims to present the existing literature on forest policy directions on land use change, forestry, and the utilisation of forests as carbon sinks for Mediterranean countries. Another objective is to review current trends and identify challenging issues that lead to policy gaps. A scoping review and analysis were conducted based on a pre-determined research question. Scopus was used as the search database, and descriptive statistics were applied for data processing. The study finds that the forestry sector is most cited for its high potential in climate change mitigation and resilience planning. However, forest industry models aiming at climate neutrality are the least cited schemes in the literature. If the main goal for Mediterranean countries is to efficiently meet the current and future targets for their international pledges and to ensure a responsible position in a greener planet, forest policy re-construction should be listed at the top of the agenda of policy-makers. Highlights: Forestry is the most cited era in climate mitigation and resilience planning. Forest industry models aiming in climate neutrality is the least cited scheme in literature. Land policies should trigger afforestation, and discourage deforestation - forest degradation. Bottom – up participatory model with the engagement of multilevel stakeholders. Mediterranean forest inventory; monitoring systems; big data validation.